An investigation of long time lags to breakdown in short vacuum gaps - Ahmad Darus, Prof Dato'; University of Strathclyde. Department of Electrical Engineering (1982)
Thesis (Sarjana Sains (Kejuruteraan Elektrik)) - University of Strathclyde, 1982